Sorghum seed storage in Purdue Improved Crop Storage (PICS) bags and improvised containers. (May 2017) - Williams, Scott B.; Murdock, Larry L.; Baributsa, Dieudonne
Abstract: Seed storage is a major challenge for smallholder farmers in developing nations. Purdue Improved Crop Storage (PICS) bags effectively control the postharvest insect pests of cowpea and other crops. Farmers, encouraged by this success, have begun to expand the use of PICS bags for storing other crops. Little is known about how sorghum seed, one of these important crops, fares when stored under hermetic conditions. Accordingly, we stored sorghum seed for six months in either airtight containers (PICS bags or sealed plastic bottles) or open ones (woven polypropylene bags and open plastic bottles). Overall, sorghum seed stored in PICS bags and in sealed plastic bottles maintained its initial moisture level, germination rate and seed weight. Porous polypropylene bags and open plastic bottles lost moisture over six months. We conclude that sorghum seed can be safely stored in hermetic containers without any loss of quality for extended periods of time. Highlights: Sorghum was stored in PICS and woven bags and tested for quality after 6 months. Plastic soda bottles were also tested as storage containers. Storage in hermetic containers had no effect of metrics of grain quality. Sorghum can be safely stored in hermetic containers.